Comparative study of direct and indirect bonding techniques of brackets in orthodontics (Research, Society and Development, 2023)
The present study aimed to compare the descriptions of both direct and indirect bracket bonding techniques in order to highlight their advantages and disadvantages. The methodological approach involved systematic research on the Pubmed and Virtual Health Library (BVS) platforms. Inclusion criteria considered experimental articles that utilized direct or indirect bonding techniques in orthodontic patients, published in Portuguese or English, up to 2022. Excluded from the review were abstracts, event proceedings, dissertations, monographs, theses, and books that did not address the topic. Based on the inclusion criteria, 234 studies were initially selected based on the reading of titles and objectives. After removing duplicate articles and those that did not meet the established criteria, 32 articles were selected for full reading, and of these, 11 studies were included in the study for meeting all the necessary requirements. The indirect technique made the orthodontic bracket bonding phase more efficient, reducing patient treatment time. However, both direct and indirect techniques demonstrated precision in bonding and shear strength resistance, as well as equivalent failure rates.